Optimizing the preparation of nanoemulsions based on sacha inchi (Plukentia volubilis L.) seed oil by response surface methodology - Dam, Xuan Thang; Cung Dinh Duc; Nguyen Ngoc Quynh; Pham Thi Tham; Thai Hoang; Nguyen Phi Hung; Nguyen Thuy Chinh (Vietnam Journal of Science and Technology, 2025)
This work presents the use of Sacha Inchi (Plukentia volubilis L.) seed oil (SO) as an oily phase for preparation of nanoemulsion systems. The pseudo-ternary phase diagram for SO, water and surfactants has been constructed to find the suitable range for components of the emulsion systems. The optimization has been processed to investigate the optimal composition of components of the emulsion systems. The emulsion prepared based on SO, Tween 80 and distilled water had a high stability without layer separation after 30 days of testing. Therefore, three technology factors including SO volume, Tween 80 volume and distilled water volume with low level (-1) and high level (+1) have been selected while the droplet size was used as a objective function. The quadratic design model and analysis of variance (ANOVA) statistical model have been calculated based on the data of droplet size obtained from 15 randomized experiments. The optimization was carried out by using Design Expert 11.1.0.1 software and Box-Behnken design type by response surface methodology (RSM). The results showed a high fitting of theoretical model and experimental data. The optimal conditions were found at SO of 266 µL, Tween 80 of 264 µL, and distilled water of 483 µL. At the optimal conditions, the droplet size of the submicron emulsion was 57.9 ± 1.5 nm. Other characteristics of the nanoemulsion prepared at the optimal conditions have been evaluated by using the infrared (IR) spectroscopy, stereo microscopy (SM), zeta potential and ultra violet visible (UV-Vis) spectroscopy.